UTILIZATION OF TOFU AND TAPIOCA INDUSTRIAL LIQUID WASTE FOR NILE TILAPIA (Oreochromis niloticus) CULTURE WITHIN DIFFERENT BIOFLOC SYSTEMS - Suryo Kunindar; Eko Efendi; Supono Supono (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2018)
Liquid waste produced by tofu and tapioca industry was approximately 1,5-2 m3 and 4-6 m3 per day respectively. Tapioca liquid waste has concentration of carbon around 119,11 mg/l, while tofu liquid waste has around 133,03 mg/l of nitrogen in concentration. Therefore both of these waste have the potential to be used as biofloc that utilized as additional feed with high protein content for nile tilapia. The aim of this research was to know interaction between C/N ratio and place of biofloc production to the growth of nile tilapia. This research used completely randomized design based on factorial experiment which consisted of two level of each factor and three repetition. Level of C/N ratio were 15 and 20 whereas level of place of biofloc production were inside and outside fish culture container. The result of this research showed that interaction between place of biofloc production and C/N ratio affected the growth of nile tilapia. The treatment inside biofloc production with 20 C/N ratio gave provided the highest absolute growth (3,26 g) and daily growth rate (0,082 g per day).